Síntesis de aminoácidos marcados: I.Síntesis de DL-Valina-1-C(14) y DL-Leucina-1-C(14) - Bühler, M.F.; Mitta, A.E.A.; Dankert, M.A.; Castrillón, J.P.A. (Comisión Nacional de Energía Atómica (CNEA), 1960)
Fil:Bühler, M.F. Comisión Nacional de Energía Atómica (CNEA). República Argentina